Exploring the barriers to the use of blackboard learning system at Arar University College in Saudi Arabia - Almijlad, Aliyah Kayyad Hakem; Muhamad, Mohd Mokhtar; Md. Khambari, Mas Nida (Secholian Publication, 2022)
The success of lecturers in adopting innovation in this age of digitization has a direct impact on their student's academic performance and, ultimately, institutional goals. However, many teachers have not integrated technological resources into their classrooms, such as the Blackboard learning system. As a result, this article explored lecturers' perspectives on potential obstacles to the use of the Blackboard in teaching. The study was carried out at Arar University College in the Kingdom of Saudi Arabia in the 2021-2022 academic session. Semi-structured interviews were conducted with nine lecturers. Findings indicate that technological, institutional, and cultural barriers as the main themes that emerged from the lecturers’ interviews. Thus, for effective utilization of the blackboard system, there is a need for technological advancement in both hardware and software infrastructures, continuous technical support, training, and institutional commitments of the government of Saudi Arabia and Arar university college in particular. Moreover, the design and development of software should bridge gender gaps and retain the cultural norms of the kingdom of Saudi Arabia.